FAW-Volkswagen Audi : an overall definer of "luxury" cars in China (2001-2011) - McFarlan, F. Warren (Franklin Warren); Jiao, Jie; Cao, Shanshan; Miao, Shuo; Jiao, Hao (London : Tsinghua University School of Economics and Management, 2016)
The FAW-Volkswagen Audi "trilogy" case describes Audi's development history in China and the problems it faces currently, as well as demonstrating the strategies employed by FAW-Volkswagen Audi in their thirty year business partnership. Between 2001-2011 FAW-Volkswagen Audi launched the "localization of the whole value chain" strategy, that is, localization in product development, procurement, production, marketing and other sectors. This strategy further guaranteed product quality while effectively reducing costs. The case focuses on how Audi responded to increased competition in the Chinese auto-industry, especially from other German car brands such as BMW.
Originally Published InMcFarlan, F. W., Jiao, J. Cao, S., Miao, S., & Jiao, H. (2016). FAW-Volkswagen Audi: An overall definer of "luxury" cars in China (2001-2011). 0-516-312. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Volkswagenwerk; Audi AG; Automobile industry and trade -- China; Industrial efficiency; Factory management